Peran Miscible Gas Flooding dalam Meningkatkan Akumulasi Produktivitas Sumur Minyak - Edy Soesanto; Muhammad Rifda Hasandra; Anis Riski Yulianti (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Oil production from a reservoir will naturally decrease or even not be able to produce at all. This condition does not necessarily indicate that the oil reserves in the reservoir have run out. If we only rely on primary production methods (primary recovery), it is likely that there is still a lot of oil left in the reservoir, so advanced production methods are needed to be able to drain the oil that is still left in the reservoir. Advanced oil recovery technology or Enhanced Oil Recovery (EOR) continues to develop to overcome the challenges in increasing oil production from reservoirs that have entered the secondary or tertiary production stage. One method that has attracted attention is Miscible Gas Flooding (MGF), which involves injecting certain gases into the reservoir. This method allows the creation of perfect mixing conditions (miscible) between the injected gas and the oil in the reservoir, thereby increasing the efficiency of oil transfer and maximizing recovery results. This technology is a solution to maximize the potential of oil wells that have experienced decreased productivity. The main principle of Miscible Gas Flooding is to reduce the interfacial tension between oil and gas, and reduce the viscosity of the oil, so that the oil can flow more easily to the production well. Commonly used gases include carbon dioxide (CO₂), nitrogen (N₂), or light hydrocarbons such as methane and ethane. With the right pressure and temperature, these gases can mix homogeneously with oil, resulting in higher displacement efficiency compared to water or immiscible gas injection methods. These advantages make MGF one of the most effective approaches to increase oil well productivity in complex reservoirs. Although promising, the implementation of Miscible Gas Flooding requires careful planning and a comprehensive evaluation of reservoir conditions. Factors such as the minimum pressure to achieve miscibility, the type of gas used, and potential disturbances such as fingering or channeling must be carefully considered. In addition, operational costs and the infrastructure required are also aspects that need to be taken into account.